Difference of Precocious Puberty Between Before and During the COVID-19 Pandemic: A Cross-Sectional Study Among Shanghai School-Aged Girls - Chen, Yao; Chen, Jianyong; Tang, Yijun; Zhang, Qianwen; Wang, Yirou; Li, Qun; Li, Xin; Weng, Zihan; Huang, Ju; Wang, Xiumin; Liu, Shijian (Frontiers in Endocrinology, 2022)
Objective To compared the incidence rates and clinical features of precocious girls before and during the COVID-19 pandemic among Shanghai school-aged girls, and explored the potential mechanisms. Methods This cross-sectional study collected medical data about precocious girls between 2016 and 2020 from Shanghai Children’s Medical Center. Data of inpatient precocious girls from March to August in 2016-2019 (n=246) and 2020 (n=237) were collected. Subjects with abnormal brain and pituitary gland MRI reports, other endocrine diseases or chronic diseases were excluded. Finally, 209 precocious girls were included in the 2016-2019 group and 191 precocious girls were include in the 2020 group. Monthly incidence rates and clinical features were compared between before and during the COVID-19 pandemic. Linear regression models were used to examine the associations between biomarkers to explore the potential mechanisms. Results Monthly incidence rates of precocious puberty in outpatient girls from March to December 2020 (0.44-1.36%) and in inpatient girls from March to August 2020 (27.04-47.83%) were higher than those in 2016-2019 (0.30-0.52% and 10.53-18.42%, respectively). Serum concentrations of GnRH were higher in the 2020 group than in the 2016-2019 group (2.81 vs 1.99 mg/L). Serum concentrations of MKRN3 (1.02 vs 1.93 ng/ml) and ghrelin (0.38 vs 0.88 ng/ml) were lower in the 2020 group than in the 2016-2019 group. Moreover, the serum concentration of ghrelin was positively associated with the serum concentration of MKRN3 [β=0.891 (95% CI, 0.612, 1.171); p<0.001]. Conclusions These findings suggest an increased incidence of precocious puberty during the COVID-19 pandemic among Shanghai school-aged girls, which may be associated with decreased serum concentrations of MKRN3 and ghrelin, and indicated ghrelin as a potential regulatory mechanism of puberty.